The mediating role of professional commitment on teacher contextual factors and science teacher performance in Indonesia - Irwandani Irwandani; Ardian Asyhari; Misbah Misbah; Heru Juabdin Sada; Dominikus Djago Djoa; Nurul Hidayati Murtafiah; Muhammad Aridan (Intelektual Pustaka Media Utama, 2026)
Teacher performance is critical to educational success, particularly in Indonesia’s science education landscape. This study explores the mediating role of professional commitment in the relationship between teacher contextual factors—job satisfaction, pedagogical beliefs, and perceived support—and science teacher performance. Using social exchange theory (SET) as the theoretical foundation, data were collected from 288 science teachers across Indonesia and analyzed using structural equation modeling (SEM) via SmartPLS 4.0. The results reveal that pedagogical beliefs strongly predict professional commitment (β=0.583, p0.001), while job satisfaction significantly influences both professional commitment (β=0.280, p=0.006) and teacher performance (β=0.283, p=0.002). Professional commitment itself has a strong effect on performance (β=0.536, p0.001) and mediates the indirect effects of job satisfaction (β=0.150, p=0.008) and pedagogical beliefs (β=0.312, p0.001) on teacher performance. Conversely, perceived support weak direct and indirect effects. These findings underscore the importance of fostering professional commitment through improved job satisfaction and culturally grounded pedagogical development. Policy implications include reinforcing institutional support systems, especially in underserved regions, to boost science teacher effectiveness and national science, technology, engineering, and mathematics (STEM) competitiveness.